2011
DOI: 10.1097/mbc.0b013e32834ad7bc
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer cell and microparticle procoagulant surface characterization

Abstract: Advanced pancreatic cancer is associated with a high risk of patients developing venous thromboembolism. This increased risk is thought to be tumour-driven and associated with tissue factor (TF) and microparticles. The aim of this study was to investigate the role of TF and phospholipid expression in the procoagulant properties of pancreatic cell lines and microparticles. Pancreatic cancer cell lines (MIA-PaCa-2, ASPC-1 and CFPAC-1) were assessed for expression of TF and microparticle release. Procoagulant pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Microparticles derived from monocytes are also known to carry tissue factor and are able to initiate and support coagulation [15]. An increase in microparticles has been demonstrated in various thrombotic scenarios such as acute coronary syndrome and cancer [16,17]. However, here, we show for the first time that this is true in ALF as well, thus contributing to thrombotic potential in these patients.…”
Section: Discussionmentioning
confidence: 45%
“…Microparticles derived from monocytes are also known to carry tissue factor and are able to initiate and support coagulation [15]. An increase in microparticles has been demonstrated in various thrombotic scenarios such as acute coronary syndrome and cancer [16,17]. However, here, we show for the first time that this is true in ALF as well, thus contributing to thrombotic potential in these patients.…”
Section: Discussionmentioning
confidence: 45%
“…PDA pathobiology is marked by high exposure of surface PS and up-regulation of full-length Tissue Factor (flTF), an obligatory enzymatic cofactor for serine protease fVIIa and the main trigger of blood clotting which, together with high surface PS levels, is believed to be major contributing factors to high rates of thrombosis in PDA. 57 We recently showed that a minimally coagulant alternatively spliced form of TF (asTF), also expressed at high levels in PDA lesions, promotes tumor growth and spread non-proteolytically, acting as an integrin ligand. 52 Because both flTF and asTF contribute to tumor growth and spread, as does PS, we sought to examine whether EF24 and/or UBS109 exhibit cytotoxic activity against four human PDA lines: Mia-PaCa-2 (high surface PS, no fl/asTF); ASPC-1(low surface PS, more flTF than asTF); Pt45P1 (medium surface PS, more flTF than asTF), and Pt45P1/asTF+ (medium surface PS, flTF approximately equals asTF).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of cancer cell lines to clot plasma is abrogated by incubating with a TF-blocking antibody, or with Annexin V, which blocks the binding of coagulation factors to the PS-containing cancer cell membrane (Berny-Lang et al, 2011). Further, the clotting kinetics for plasma spiked with cancer cells is strongly dependent upon the number of cells added (Tormoen et al, 2011; Yates et al, 2011; Welsh et al, 2012). Therefore, it appears that cancer cells are wholly capable of cell-mediated coagulation in vitro , whereby they can initiate coagulation through surface expression of TF and facilitate the propagation of coagulation by binding and assembling coagulation factor complexes upon their cell membranes.…”
Section: Introductionmentioning
confidence: 99%